Analisis Kemampuan Memimpin Peserta Didik pada Materi Gotong Royong di Sekolah Dasar - Hikmah, Putri Durrotul (FONDATIA, 2024)
This study aimed to explore how "gotong royong" activities can enhance leadership skills among elementary school students, particularly in terms of collaboration, initiative, responsibility, and communication. The main issue addressed is the underutilization of "gotong royong" as a tool for developing students' leadership skills, despite its significant potential in shaping students' character and social abilities. To address this issue, the study used a qualitative descriptive case study approach, involving 30 purposively selected fifth and sixth-grade students. Data were collected through observations and interviews to assess the students' participation in weekly "gotong royong" activities. The findings show that active participation in "gotong royong" significantly enhances leadership skills, particularly in collaboration, initiative, and responsibility. However, communication skills, such as listening and responding to others' opinions, still require further improvement. The implications of these findings suggest that "gotong royong" activities can be optimized as a method for leadership development in elementary education, highlighting the importance of integrating character education and leadership training more effectively into the elementary school curriculum.